Web-Based E-Learning System Design with Integrated Webinar Features at STIT Al-Falah Rimbo Bujang - Habibi Ul Akbar; Benni Purnama; Dodo Zaenal Abidin (MALCOM: Indonesian Journal of Machine Learning and Computer Science, 2026)
This study examines challenges faced by STIT Al-Falah Rimbo Bujang in implementing online learning that is not yet optimally integrated. Students and lecturers currently rely on multiple platforms such as WhatsApp, Zoom, email, and Google Drive to manage schedules, learning materials, assignments, and communication. This platform fragmentation leads to operational inefficiencies, coordination difficulties, limited monitoring, and decreased student engagement. Observations and interviews with academic administrators identified three main problems: the need to access multiple applications for a single course, the lack of automated attendance recording during webinar sessions, and inefficient assignment submission and grading via private messaging, which increases administrative workload and the risk of data loss. A student satisfaction survey conducted in the even semester of the 2023/2024 academic year showed that these issues reduced the effectiveness of online learning by up to 40%. To overcome these problems, this study proposes the design of a web-based e-learning system with integrated webinar features that centralizes learning activities into a single platform. The system is developed using the waterfall model, including requirement analysis, system design, implementation, testing, and maintenance. UML is applied for system modeling, while PHP, MySQL, and Bootstrap are used for implementation